PENGARUH KONSENTRASI DAN LAMA PERLAKUAN PUTRESIN TERHADAP PERUBAHAN KUALITAS BUAH PISANG AMBON - Bambang S. Purwoko; S. Gunadi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
Polyamines have been reported to have a role in habiting senescene. Polyamine application inhibited fruit softening and extend fruit shelflife. The common polyamine included putrescine, spermidine, and spermine. The objective of the present study was to determine the effect of concentration and length putrescine application on some quality changes in banana. The result showed that putrescine had some effects on weight loss, inhibited fruit softening, and color development. However, the effect were not consistent. The best concentration and length of application could not determine. It was suggested that pressure infiltration was used for polyamine application